Students’ challenges and mitigation factors during COVID-19 pandemic on teaching and learning method / Aida Hazlin Ismail, Nadiah Abdul Hamid and Zarinah Abdul Rasit - Ismail, Aida Hazlin; Abdul Hamid, Nadiah; Abdul Rasit, Zarinah (Faculty of Communication & Media Studies, 2024)
The research focuses on identifying challenges and problems faced by the students experiencing the online learning during pandemic covid 19. In this regard, this paper aims to identify factors that may influence online learning among the university students, their perceptions on online learning and the use of E-learning platforms. An online survey based on a semi-structured questionnaire was conducted. Data was collected from 153 students from one of the public universities in Malaysia. The results of the research revealed that students are facing challenges with the online learning. Internet connections, incompatible gadget to join the online lecture are some of the challenges faced by the students. This is to help the students to watch the video during their revision time. Technical issues are the most important, followed by teachers’ lack of technical skills and their teaching style improperly adapted to the online environment. However, students provide some suggestions to improve the situation such as for the lecturers to provide recorded lecture video after each learning session and creating interesting lecture using the information technology applications and facilities. Based on these findings, research implications for universities and researchers are discussed.